2021
DOI: 10.7554/elife.70907
|View full text |Cite
|
Sign up to set email alerts
|

Respiration aligns perception with neural excitability

Abstract: Recent studies from the field of interoception have highlighted the link between bodily and neural rhythms during action, perception, and cognition. The mechanisms underlying functional body-brain coupling, however, are poorly understood, as are the ways in which they modulate behaviour. We acquired respiration and human magnetoencephalography (MEG) data from a near-threshold spatial detection task to investigate the trivariate relationship between respiration, neural excitability, and performance. Respiration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 79 publications
(118 reference statements)
4
106
0
Order By: Relevance
“…Further, to the extent that interoceptive signals (as modeled by the brain) act as control signals for allostasis (Sennesh et al, 2021), those signals may also play a role in the sampling of unanticipated exteroceptive signals (i.e., exteroceptive prediction errors). This hypothesis is supported by evidence that sampling of visual, auditory, and other data from the sensory surfaces of the body is statistically related to bodily signals such as heart beats and respiration (e.g., Al et al, 2020;Aspell et al, 2013;Galvez-Pol et al, 2020;Grund et al, 2021;Kluger et al, 2021;Kunzendorf et al, 2019;Zelano et al, 2016).…”
Section: The Brain's Intrinsic System For Allostasismentioning
confidence: 90%
“…Further, to the extent that interoceptive signals (as modeled by the brain) act as control signals for allostasis (Sennesh et al, 2021), those signals may also play a role in the sampling of unanticipated exteroceptive signals (i.e., exteroceptive prediction errors). This hypothesis is supported by evidence that sampling of visual, auditory, and other data from the sensory surfaces of the body is statistically related to bodily signals such as heart beats and respiration (e.g., Al et al, 2020;Aspell et al, 2013;Galvez-Pol et al, 2020;Grund et al, 2021;Kluger et al, 2021;Kunzendorf et al, 2019;Zelano et al, 2016).…”
Section: The Brain's Intrinsic System For Allostasismentioning
confidence: 90%
“…To conclude, in line with the active sensing interpretation of respiratory activity, we speculate on the existence of a breathing-related attentional “switch” between interoceptive and exteroceptive brain modalities. It is already known that inhalation leads to adaptive modulation of neuronal gain in order to facilitate reception and elaboration of sensory information from the external environment (Grund et al, 2021; Huijbers et al, 2014; Kluger et al, 2021; Perl et al, 2019; Zelano et al, 2016). As inhalation itself improves exteroception-related cognitive functions, exhalation may reflect a more general attentional shifts towards the internal bodily states and the self, hence modulating interoceptive perception as well as self-consciousness (Molle and Coste, 2022; Park et al, 2018; Park and Blanke, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zelano et al (2016) found increased emotional recognition and episodic memory encoding and retrieval during inhalation, as compared to exhalation. Accordingly, phase-locking of stimulus onset to inhalation increased participant’s near-threshold somatosensory perception (Grund et al, 2021) visuospatial recognition abilities (Kluger et al, 2021; Perl et al, 2019), and memory performance (Huijbers et al, 2014). Differently, self-initiated motor actions (Park et al, 2020), and trace eyeblink conditioning learning (Waselius et al, 2019) were more frequent during exhalation, while the exhalation-to-inhalation phase transition improved recognition memory performance (Nakamura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, an alignment between human participants and behaviour has been also shown in another facet of the cardiovascular system, i.e., respiration. Perl et al, (2019) showed the alignment of self-initiated cognitive tests with the beginning of the inspiratory phase, and recent work by Kluger et al, (2021) has shown respiration-locked performance in a near-threshold spatial detection task.…”
Section: Coupling Between Active Sensing and Transient Bodily Cyclesmentioning
confidence: 90%
“…This might include, for instance, heartbeat, motor-cortical, and/or somatosensory-evoked activity (e.g., Al et al, 2020;Galvez-Pol et al, 2018Montoya et al, 1993;Park & Blanke, 2019). As described in Kluger et al, (2021), bodily-entrained fluctuations in neural activity may represent a mechanism for uniting neural and behavioural findings. While evidence for this account has been accumulating in the animal literature, specially between the respiratory cycle and behaviours (Kurnikova et al, 2017;Moore et al, 2013), the field of active sensing in humans with physiological measures remains largely uncharted.…”
Section: Constraints Of Generality and Future Workmentioning
confidence: 99%